Laporan lawatan ke tapak pembinaan bangunan - Abu Hassan Shaari A.K.,; Ahmad Zaidi ZA.,; Mohd Ismail L.,; Rokian M., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1994)
A visit to a construction site was conducted with the objective of observing the working envioronment as well as to identify the occupational hazards faced the constructuion workers. The main hazards identified are accidents, noise, dust, heat, solvents, metal fume, plumbum, ergonomic and pshycho-social. Safety measures need to be strenghthened and workers including employees of the sub-contractors need to obey and follow all the safety measures as long as they are working at the construction site. The effor tto investigate all accident ceses is useful in accident prevention. However the provision of 'rumah kongsi' and the office at the basement and ground floor needs review. Health education and training of workers in accident prevention and occupational health should be conducted on regular basis.